The reliability of FEbrile Neutropenia after ChEmotherapy (FENCE) scores in predicting granulocyte colony-stimulating factor breakthrough febrile neutropenia among patients with lymphoma undergoing first-cycle chemotherapy: A prospective observational study - Thungthong, Pravinwan; Chamnanchanunt, Supat; Suwanban, Tawatchai; Nakhahes, Chajchawan; Iam-arunthai, Kunapa; Akrawikrai, Tananchai; Bunworasate, Udomsak; Rojnuckarin, Ponlapat (Frontiers in Medicine, 2023)
Background: Estimate of febrile neutropenia (FN) after chemotherapy has been developed using the FEbrile Neutropenia after ChEmotherapy (FENNCE) score but has not been widely validated. This study aimed to validate the FENCE score for predicting granulocyte colony-stimulating factor (G-CSF) breakthrough FN among patients with lymphoma who underwent chemotherapy. Methods: This was a prospective observational study of treatment-naïve adult patients with lymphoma who underwent the first-cycle of chemotherapy between 2020 and 2021. The patients were followed up until the next cycle of chemotherapy to identify any infection events. Results: Among the 135 patients with lymphoma, 62 (50%) were males. Compared with each FENCE parameter for predicting G-CSF breakthrough infection, the advanced stage showed high sensitivity of 92.8%, and patients received platinum chemotherapy showed high specificity of 95.33%. With a cutoff point of 12 of the FENCE score as low-risk, all patients with lymphoma demonstrated a high AUROCC of 0.63 (95%CI=0.5-0.74%; p= 0.059), and patients with only diffuse large B-cell lymphoma (DLBCL) demonstrated AUROCC of 0.65 (95%CI=0.51-0.79%; p= 0.046). FENCE score at a cutoff point of 12 can predict infection events breakthrough at 30.0% (95%CI=17.8-47.4%). Conclusions: This study divided patients with lymphoma according to FENCE risk groups, showing a discriminatory ability to predict FN events for patients with intermediate- and high-risk groups. Multicenter studies are needed to validate this clinical risk score.